Implementasi Model Pembelajaran Problem - Based Learning Pada Pembelajaran Pendidikan Agama Islam di Kelas VIII SMP IT Ar-Ridha Pantai Cermin - Muamar Al Qadri; Rudi Irawan; Ratika Dewi; Khairunnisa Khairunnisa; Siti Zulaiha (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the application of the Problem Based Learning (PBL) learning model in increasing the activeness and understanding of students in Islamic Religious Education subjects at SMP IT Ar-Ridha Pantai Cermin. The method used is descriptive qualitative research with a field approach. Data collection was done through observation, interviews, and documentation, and using Miles and Huberman data analysis techniques. The research subjects included Islamic Religion teachers and class VIII students. The results showed that the application of PBL succeeded in increasing the activeness and enthusiasm of students, reducing boredom, and deepening understanding of the material through solving problems relevant to everyday life. Supporting factors for the implementation of PBL include the availability of adequate learning resources and the active involvement of students, while inhibiting factors include limited time and learning facilities. PBL implementation also involves five main stages, namely orientation to the problem, organising students, guiding investigation, presenting results, and evaluation.